Macroalgae Community Structure in West Coastal Waters of Kelabat Outer Bay, West Bangka District - Sapitri; Anggraeni; Akhrianti, Irma (Jurnal Ilmiah Platax, 2023)
The waters of the Bangka Belitung Islands, including the small islands around them, are areas with great potential for macroalgal growth. One of these areas is the waters of Kelabat Bay. Research on macroalgae in Kelabat Bay has previously been carried out, but the data obtained was not complete, so further research is needed. The purpose of this study is to identify the types of macroalgae and analyze the macroalgae community structure, as well as the relationship between physicochemical factors in the waters and the macroalgae community structure in the est coastal waters of Kelabat Outer Bay, West Bangka Districts. The location of the research station was determined by the purposive sampling method. The macroalgae sampling method is a systematic, random method of spreading line transects. Based on research results, the most abundant macroalgae found in the western coastal waters of Kelabat Outer Bay are from the Phaeophyta division, totaling 8 species with a total of 1,637 individuals; the Chlorophyta division, consisting of 4 species with a total of 692 individuals; and the Rhodophyta division, composed of 2 species with a total of 140 individuals. Which has the highest number of individuals, is Sargassum muticum, which amounted to 697 individuals. The diversity index of macroalgae in the west coastal waters of Kelabat Outer Bay is in the medium category (1,69–2,05), the evenness index is high (0,77–0,84), and the dominance index is low (0,16–0,24). Physico-chemical parameters of the waters that affect the macroalgal community structure based on principal component analysis include current velocity, salinity, and brightness. Keywords: macroalgae; community structure; Kelabat Bay Abstrak Perairan Kepulauan Bangka Belitung dan termasuk pulau-pulau kecil di sekitarnya merupakan daerah yang sangat potensial bagi pertumbuhan makroalga. Salah satu daerah tersebut adalah Perairan Teluk Kelabat. Penelitian tentang makroalga di Teluk Kelabat sebelumnya pernah dilakukan, tetapi data yang diperoleh belum lengkap sehingga perlu dilakukan penelitian ulang. Penelitian ini bertujuan untuk mengidentifikasi jenis-jenis makroalga dan menganalisis struktur komunitas makroalga serta hubungan faktor fisika-kimia perairan terhadap struktur komunitas makroalga yang terdapat di perairan pesisir barat Teluk Kelabat Luar, Kabupaten Bangka Barat. Lokasi stasiun penelitian ditentukan dengan metode purposive sampling. Metode pengambilan sampel makroalga adalah metode acak sistematis dengan membentangkan transek garis. Berdasarkan hasil penelitian, makroalga yang paling banyak ditemukan di perairan pesisir barat Teluk Kelabat Luar adalah dari divisi Phaeophyta sebanyak 8 spesies dengan total individu sebanyak 1.637, divisi Chlorophyta sebanyak 4 spesies dengan total individu sebanyak 692 dan divisi Rhodophyta sebanyak 2 spesies dengan total individu sebanyak 140. Jenis makroalga yang memiliki jumlah individu terbanyak adalah Sargassum muticum yang berjumlah 697 individu. Indeks keanekaragaman makroalga di perairan pesisir barat Teluk Kelabat Luar termasuk dalam kategori sedang (1,69–2,05), indeks kemerataan tergolong tinggi (0,77–0,84), dan indeks dominansi tergolong rendah (0,16–0,24). Parameter fisika-kimia perairan yang berpengaruh terhadap struktur komunitas makroalga berdasarkan analisis komponen utama meliputi kecepatan arus, salinitas dan kecerahan. Kata kunci: makroalga; struktur komunitas; Teluk Kelabat.